The clinical significance of drug–drug interactions in the era of direct‐acting anti‐viral agents against chronic hepatitis C. Issue 11 (16th October 2013) - Maasoumy, B.; Port, K.; Calle Serrano, B.; Markova, A. A.; Sollik, L.; Manns, M. P.; Cornberg, M.; Wedemeyer, H.
Summary: Background: Drug–drug interactions (DDIs) in the treatment of chronic hepatitis C infection became a potential challenge with the introduction of direct‐acting anti‐virals (DAAs). Both currently approved DAAs, the protease inhibitors (PIs) telaprevir (TVR) and boceprevir (BOC), are substrates and inhibitors of P‐glycoprotein and the cytochrome P450 3A4, which are regularly involved in DDIs. Aim: To analyse the risk for DDIs in patients with chronic HCV genotype 1 infection considered for PI treatment at a tertiary referral centre. Methods: The first 115 consecutive patients selected for a PI therapy at Hannover Medical School were included. All changes to co‐medication before and during PI treatment were documented. Drugs were checked for DDIs with TVR and BOC using DDI websites and the respective prescribing information. Results: Out‐patient medication contained 116 different drugs. Median number of drugs/patient was 2 (range 0–11). The risk for DDIs was substantial for 38% of the drugs affecting 49% of patients. Only 4% of the drugs were strictly contraindicated. DDIs between a PI and drugs newly prescribed during anti‐viral therapy were considerable in 42% of the patients. Suspected DDIs were managed by dose adjustments and discontinuation of co‐medication in 7% and 21% of the patients respectively. Conclusions: Many patients with chronic HCV genotype 1 infection are affected by potential DDIs if treated with a protease inhibitor, but only in a minority of cases co‐medication is strictly incompatible. Overall, the challenge of DDIs is time‐consuming, but well manageable by a careful review of the patient's drug chart and monitoring during treatment.